Physiologically Based Simulations of Deuterated Glucose for Quantifying Cell Turnover in Humans - Lahoz-Beneytez, Julio; Schaller, Stephan; Macallan, Derek; Eissing, Thomas; Niederalt, Christoph; Asquith, Becca (Frontiers in Immunology, 2017)
In vivo [6,6-2H2]-glucose labelling is a state of the art technique for quantifying cell proliferation and cell disappearance in humans. However, there are discrepancies between estimates of T cell proliferation reported in short (one-day) versus long (seven-day) 2H2-glucose studies and very-long (9-week) 2H2O studies. It has been suggested that these discrepancies arise from underestimation of true glucose exposure from intermittent blood sampling in the one-day study. Label availability in glucose studies is normally approximated by a “square pulse”. Since the body glucose pool is small and turns over rapidly the availability of labelled glucose can be subject to large fluctuations and the square pulse approximation may be very inaccurate. Here we model the pharmacokinetics of exogenous labelled glucose using a physiologically based pharmacokinetic (PBPK) model to assess the impact of a more complete description of label availability as a function of time on estimates of CD4+ and CD8+ T cell proliferation and disappearance. The model enabled us to predict the exposure to labelled glucose during the fasting and de-labelling phases, capture the fluctuations of labelled glucose availability caused by the intake of food or high-glucose beverages, and to re-calculate the proliferation and death rates of immune cells. The PBPK model was used to reanalyse experimental data from three previously published studies using different labelling protocols. Although using the PBPK enrichment profile decreased the one-day proliferation estimates by about 4% and 7% for CD4 and CD8+ T cells, respectively, differences with the seven-day and 9-week studies remained significant. We conclude that the approximations underlying the “square pulse” approach – recently suggested as the most plausible hypothesis– only explain a component of the discrepancy in published T cell proliferation rate estimates.